1978
DOI: 10.1111/j.1365-2621.1978.tb15250.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Microbial Growth in Ground Beef Extended With Varying Levels of Textured Soy Protein

Abstract: Three separate batches of ground beef containing 25% fat were extended to 0, 10, 20 and 30% by weight with rehydrated defatted textured soy protein (TSP). Five samples of each soy level were wrapped in a polyethylene oxygen-permeable film and stored at 5°C for 4 days. Samples were analyzed daily for changes in bacterial numbers (total plate counts and coliforms), pH, titratable acidity, proximate analysis, ninhydrin reactive material, carbohydrate content, and gas liquid chromatographic (GLC) analysis of indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 18 publications
2
10
1
1
Order By: Relevance
“…This may be attributed to increased availability of carbohydrate for lactic acid bacteria (particularly in weeks 1 and 2) in samples containing higher levels of melon. Similar results for soy extended ground beef were obtained by Keeton and Melton (1978). Variation in the bacterial growth between levels of extension and storage period could be attributed to the differences in pH and water‐holding capacity, both of which were affected by level of melon addition.…”
Section: Discussionsupporting
confidence: 87%
“…This may be attributed to increased availability of carbohydrate for lactic acid bacteria (particularly in weeks 1 and 2) in samples containing higher levels of melon. Similar results for soy extended ground beef were obtained by Keeton and Melton (1978). Variation in the bacterial growth between levels of extension and storage period could be attributed to the differences in pH and water‐holding capacity, both of which were affected by level of melon addition.…”
Section: Discussionsupporting
confidence: 87%
“…However, Foster et al (1978) showed no significant differences between soy extended ground beef and 100% ground beef for mesophillic, psychrotrophic, and coliform organisms. Keeton and Melton (1978) showed coliform counts were significantly higher in textured soy protein extended ground beef after one day of storage in comparison to the 100% ground beef. In our study, no differences (P~0.05) were found among ground beef pattie treatments for coliform, aerobic and psychrotrophic plate counts (data not shown).…”
Section: Tbars Evaluationmentioning
confidence: 91%
“…The pH value was measured in samples according to the method described by Krilova and Liskovskaia (1961) using a Beckman pH meter with a combined electrode and acidity was determined according to Keeton and Melton (1978). …”
Section: Determination Of Ph Value and Aciditymentioning
confidence: 99%